Cost and time reduction in the evaluation of functional failures in flexible pavements through photographic imaging and PCI methodology - Rojas, J. (2024)
Despite the importance of maintaining flexible pavements in optimal conditions to guarantee the trafficability and comfort of users, the evaluation of failures in these pavements is usually a slow and costly process.Early detection of these failures is essential to prevent them from escalating and generating higher rehabilitation costs.Furthermore, in some areas of the city of Lima, the lack of government budget and availability for road maintenance further complicates the situation.This article addresses the evaluation of functional failures in flexible pavements, incorporating the use of mobile technology and image processing through the use of the MATLAB tool compared to the conventional method of Pavement Condition Index (PCI) according to ASTM D6433.The implementation of mobile technology together with the processing of photographic images for the evaluation of the PCI of the pavement generates a saving of 44.20% of the total cost for the evaluation using the traditional method.Likewise, the implementation of this method significantly reduces the PCI evaluation time by 15% concerning the traditional method in the evaluation of functional failures in flexible pavements.